Sperm Quality of Bull Limousin (Bos taurus) in the Area of Ibuh, Payakumbuh - Muthia Oktavia; Ramadhan Sumarmin (Jurnal Serambi Biologi, 2021)
Beef cattle are cows that are specially raised for fattening because of their fast growth system and good quality aof meat. Limousine are one of the cows that have superior genetic quality. The Ibuh community began to like limousine cows because the grew rapidly and could be developed in an artificial insemination program. This cow cement can be used to produce frozen semen and distributed to other areas. The purposes of this study to determine the quality of male limousine bull sperm in the Ibuh area, Payakumbuh. The method used collection and identification at 3 bulls aged 3-4 years. Ejaculate sperm was taken once a week for 4 months to each male. There are two data analysis in this research. First parametric data were analyzed using ANOVA, and the second non-parametric data were presented in tabular form. The results showed that the mean macroscopic and microscopic sperm quality was normal, so that for parametric data (volume, pH, motility and concentration) analyzed by ANOVA, Fcount <Ftable was obtained so that it was not significantly higher at the p <0.05. It was concluded that the quality of ejaculated sperm from the limousine bull have good. Quality.